Cement-based zinc battery with low interface impedance as well as preparation method and application of cement-based zinc battery
By using 3D printing technology to print the electrode material layer in cement-based batteries, liquid metal penetrates into the pore structure of the cement-based electrolyte, the problem of poor solid-solid contact between the electrode and the electrolyte is solved, low interface impedance and long-term stability are achieved, and battery performance is improved.
Patent Information
- Application Number
- CN202411679208.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The solid-solid contact between the electrode and the electrolyte in cement-based batteries is poor, resulting in a large interface impedance and affecting the battery life and overall performance.
Through 3D printing technology, the positive and negative electrode material layers are printed on both sides of the vertical direction of the cement-based electrolyte, allowing liquid metal to penetrate into the pore structure of the cement-based electrolyte surface layer, and the adhesion strength between the cement-based electrolyte and the metal electrode is enhanced.
It significantly reduces the contact resistance between the electrode and the electrolyte interface, ensures the long-term stability of the electrode during use, improves the overall performance of the battery, and reduces the occurrence of side effects.
Smart Images

Figure CN119695302A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a cement-based zinc battery with low interfacial impedance and a preparation method and application thereof. Background Art
[0002] With the continuous development of sustainable energy technology, cement-based batteries have received more and more attention as an innovative energy storage solution. Cement-based batteries have excellent mechanical properties and the ability to convert electrical energy into chemical energy. They can be used as building blocks and alleviate dependence on traditional energy storage devices. However, the interfacial stability between cement-based electrolytes and electrodes is one of the key technologies that limits their widespread application. The solid-solid contact between electrodes and electrolytes in cement-based batteries is poor, which will cause large interfacial impedance and limit interfacial ion transport, affecting battery life and overall performance. Traditional research usually improves the interfacial stability between cement-based electrolytes and electrodes by ion doping-induced interface modification, various types of surface coatings and interlayers, external pressurization, and increased operating temperature. Specific examples include applying a wetting agent; adding a polymer interfacial layer; adding an alloy interlayer; adding a quasi-solid organic interlayer; adding a soft and ion-conductive intermediate material; applying external pressure to make the electrode and electrolyte in close contact; and increasing the operating temperature of cement-based batteries. However, its disadvantages are also obvious. The chemical modification is not stable enough; the wetting agent causes a decrease in capacity due to slight volatilization or decomposition of the organic liquid electrolyte during the cycle; the addition of polymers makes the battery safety controversial; the conductivity of the intermediate layer material is poor; and applying pressure causes material damage.
[0003] Therefore, how to improve the contact stability between electrodes and electrolytes without causing major side effects has become a current research hotspot. Summary of the invention
[0004] The purpose of the present invention is to provide a cement-based zinc battery with low interfacial impedance and a preparation method and application thereof, so as to improve the interfacial stability of the electrolyte and the electrode of the cement-based battery and reduce the interfacial impedance without causing major side effects.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] On the one hand, the present invention provides a cement-based zinc battery with low interfacial impedance, wherein the cement-based zinc battery comprises a cement-based electrolyte, and a positive electrode material layer and a negative electrode material layer are respectively melt-solidified on opposite sides of the surface of the cement-based electrolyte by 3D printing technology.
[0007] Preferably, the vertical height of the cement-based electrolyte is 15-20 mm, and the cement-based electrolyte has a directional pore structure with a pore diameter of 10-20 μm and a porosity of 20-40%.
[0008] Preferably, the pores of the directionally arranged pore structure are oriented in the same direction as the vertical direction of the cement-based electrolyte, and the positive electrode material layer and the negative electrode material layer are respectively melt-solidified on both sides of the vertical direction of the cement-based electrolyte.
[0009] In the present invention, the positive and negative electrode material layers are printed on both sides of the cement-based electrolyte in the vertical direction by using 3D printing technology, so that the liquid metal can penetrate into the pore structure of the surface layer of the cement-based electrolyte, so that the adhesion strength between the cement-based electrolyte and the metal electrode is greatly improved, and the possibility of separation at the interface under working conditions is reduced.
[0010] Preferably, the positive electrode material layer is copper and has a thickness of 2-3 mm.
[0011] Preferably, the negative electrode material layer is zinc and has a thickness of 2-3 mm.
[0012] Preferably, the cement-based zinc battery with low interfacial impedance comprises the following components in parts by mass:
[0013]
[0014] Further preferably, the cement-based zinc battery with low interfacial impedance comprises the following components in parts by mass:
[0015]
[0016] Further preferably, the cementitious material is selected from any one or more of Portland cement, fly ash, and silica fume.
[0017] More preferably, the water reducer is selected from any one or more of polycarboxylate water reducer and lignin sulfonate.
[0018] More preferably, the modifier is selected from any one or more of polyacrylamide and bentonite.
[0019] More preferably, the early strength agent is selected from any one or more of gypsum and water glass.
[0020] More preferably, the zinc powder has a particle size ranging from 45 to 150 μm.
[0021] Further preferably, the particle size of the copper powder is in the range of 45-150 μm.
[0022] In a second aspect, the present invention further provides a method for preparing the above-mentioned cement-based zinc battery with low interfacial impedance, comprising the following preparation steps:
[0023] S1, immersing cement-based material D in a zinc sulfate solution to obtain cement-based material E;
[0024] S2, removing impurities on the surface of the cement-based material E, and cleaning the surface to obtain a cement-based material F, i.e., a cement-based electrolyte;
[0025] S3, using a fixed laser scanner to scan and model the surface of the cement-based material F, and inputting the obtained model data into a coaxial powder feeding 3D printer;
[0026] S4. In an inert gas environment, a zinc electrode material layer and a copper electrode material layer are printed on opposite sides of the cement-based material F by a coaxial powder feeding 3D printer to obtain the cement-based zinc battery with low interfacial impedance.
[0027] Preferably, in step S4, the inert gas environment includes an argon gas environment.
[0028] Preferably, in step S4, after the zinc electrode material layer is printed, it is left to cool for 2-4 hours, then the cement-based material F is turned over, and the copper electrode material layer is printed on the other side. After the copper electrode material layer is printed, it is left to cool again for 2-4 hours.
[0029] Preferably, in step S4, the parameters of the 3D printing are: printing speed 5-10 mm / s, printing height 2-3 mm, and printing time 60-80 min.
[0030] Preferably, in step S3, the model data needs to be processed and converted before being input into the coaxial powder feeding 3D printer.
[0031] Preferably, in step S2, a hard brush is used to remove impurities on the surface of the cement-based material E, and the surface impurities mainly include a surface passivation layer and particles with poor adhesion.
[0032] Preferably, in step S1, the concentration of the zinc sulfate solution is 1-2M, and the immersion time is 24-48h.
[0033] Preferably, in step S1, the immersion time is related to the vertical height of the cement-based material D.
[0034] Further preferably, in step S1, the cement-based material D with a vertical height of 15 mm needs to be immersed for 24 hours, and the cement-based material D with a vertical height of 20 mm needs to be immersed for 48 hours. After being taken out, it is allowed to stand for 3 hours, and then the surface liquid is wiped off.
[0035] Preferably, in step S1, the cement-based material is prepared by the following steps:
[0036] S1.1. Mix the cementitious material, water reducing agent, early strength agent and water according to their mass proportions and stir evenly, then add the modifier and stir evenly to obtain slurry A;
[0037] S1.2. Pour slurry A into a mold with a heat conducting plate at the bottom and let it stand;
[0038] S1.3, placing the mold containing slurry A on an ultra-low temperature medium for freeze casting to quickly obtain solidified cement slurry B;
[0039] S1.4. Thaw the solidified cement paste B to obtain a block C, and then place the block C in a standard cement curing box for curing for 24 to 30 days to obtain a cement-based material D having a directional pore structure.
[0040] Further preferably, in step S1.1, the rotation speed at which the cementitious material, water reducing agent, early strength agent and water are mixed and stirred uniformly according to their mass fractions is 60±5 r / min.
[0041] Further preferably, in step S1.1, the rotation speed of mixing and stirring evenly after adding the modifier is 130±10 r / min.
[0042] Further preferably, in step S1.2, the standing time is 8-15s.
[0043] Further preferably, in step S1.3, the ultra-low temperature medium includes liquid nitrogen.
[0044] Further preferably, in step S1.3, only the thermally conductive template at the bottom of the mold is in contact with the liquid nitrogen.
[0045] Further preferably, in step S1.4, the thawing process is to place the sample in a constant temperature environment of 0-4°C for slow thawing, and the thawing time is 24-30 hours.
[0046] Further preferably, in step S1.4, when the vertical height of the block C is 15 mm, curing is required for 24 hours.
[0047] Further preferably, in step S1.4, when the vertical height of the block C is 20 mm, curing is required for 30 hours.
[0048] Traditional research has improved the interface stability between cement-based electrolytes and electrodes by ion doping, surface coating, pressurization and temperature increase, but these methods also have obvious side effects, including poor chemical stability, wetting agent volatilization, controversial polymer safety, poor conductivity of the intermediate layer and pressure damage. In the preparation process, the present invention does not use additional chemical modifications and wetting agents, nor does it add additional various types of surface coatings and intermediate layers, which reduces the possibility of side effects to a certain extent.
[0049] In a third aspect, the present invention further provides an application of the above-mentioned cement-based zinc battery with low interfacial impedance in a building component unit:
[0050] Wall components: embed low-interface-impedance cement-based zinc batteries into building walls to form load-bearing walls with energy storage functions, providing the energy storage and stable power supply required by the building, while reducing the space requirements of independent battery energy storage systems. Floors and slabs: embed cement-based zinc battery modules in building floors and slabs, which can not only bear the building load, but also provide power supply support. Rooftop solar energy system combination: cement-based zinc batteries are combined with building rooftop solar panels, and the battery modules are used as part of the roof structure to prepare energy storage modules for rooftop load-bearing brackets or insulation panels, which store solar power and provide day and night energy supply for buildings.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] (1) The present invention can increase the contact area between the cement-based material and the metal electrode by 3D printing the electrode on the surface of the cement-based material, significantly reduce the contact resistance between the electrode and the electrolyte interface, and ensure the long-term stability of the electrode during use.
[0053] (2) The present invention uses 3D printing technology to allow liquid metal to enter the micro-cracks on the solid surface, thereby greatly improving the adhesion strength between the cement-based electrolyte and the metal electrode, and reducing the possibility of separation at the interface under working conditions.
[0054] (3) The present invention omits the cutting and processing steps of traditional electrodes by directly 3D printing electrodes on cement-based materials. The preparation process is simple, material waste and energy consumption are reduced, waste generation is reduced, and good environmental benefits are achieved.
[0055] (4) No additional wetting agent is used in the preparation process of the present invention, and no additional various types of surface coatings and intermediate layers are added. Therefore, compared with the prior art, the cement-based zinc battery prepared by the present invention overcomes the defects of poor stability, volatile electrolyte, low battery safety and conductivity to a certain extent.
[0056] (5) The present invention provides a cement-based zinc battery with low interfacial impedance, which can be applied to building structures to alleviate dependence on traditional energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a 3D printed schematic diagram of the lateral path of the cement-based zinc battery with low interfacial impedance of the present invention;
[0058] Figure 2 A schematic diagram of the 3D printing route of the lateral path of the cement-based zinc battery with low interfacial impedance of the present invention;
[0059] In the figure, a-directionally arranged pore structure; b-cement-based electrolyte; 1-fixture; 2-3D printer; 3-laser; 4-metal electrode powder flow. DETAILED DESCRIPTION
[0060] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0061] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples and comparative examples are commercially available.
[0062] Example 1
[0063] In this embodiment, a cement-based zinc battery with low interfacial impedance is provided, comprising the following components in parts by weight:
[0064]
[0065] In this embodiment, the cementitious material includes the following components in percentages: 80% silicate cement, 10% fly ash, and 10% silica fume.
[0066] The water reducer is a polycarboxylate water reducer, specifically a high early strength polycarboxylate water reducer.
[0067] The modifier includes the following components in percentage by mass: 60% of polyacrylamide and 40% of bentonite, wherein the weight average molecular weight of the polyacrylamide is 10 million Daltons.
[0068] The early strength agent includes the following components in percentage by mass: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5.
[0069] The cement-based zinc battery with low interfacial impedance is prepared by the following steps:
[0070] First, 200 parts of cementitious material, 0.4 parts of water reducer, 15 parts of early strength agent and 100 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 24 hours until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 0-4°C for 30 hours to obtain block C, and block C is placed in a cement standard curing box for curing for 28 days to obtain a cement-based material D with a directional pore structure. Cement-based material D is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain cement-based material E.
[0071] After wiping off the liquid on the surface of cement-based material E, a steel brush was used to remove the passivation layer and impurities on the surface of cement-based material E to obtain cement-based material F. Figure 1 and 2 As shown, a fixed laser scanner is used to scan and model the surface of cement-based material F. The model data is processed and converted and then input into a coaxial powder feeding 3D printer. 2.5 parts of zinc powder and 3 parts of copper powder are added to the 3D printer silo respectively. The cement-based material F and the 3D printer are placed in an argon environment for printing. The 3D printer used has a laser power of 2KW and a printing speed of 5mm / s. In an argon protective environment, the 3D printer is started to ensure that the oxygen content in the printing area is controlled below 50ppm to avoid metal oxidation. The control system activates the printing program based on the imported model data. The initial printing starts from the center of the surface of the cement-based material F and proceeds along a rectangular circumferential route (such as Figure 2 As shown). The print head adjusts its height according to the modeling data, with the starting distance being 0.1mm above the highest point on the surface. Due to the different heights of each position, the amount of powder output changes accordingly, and finally the first layer of metal smoothly covers the surface, followed by layer-by-layer printing to form an actual working electrode thickness of 2-3mm. After printing the zinc electrode, let it stand and cool for 3 hours, then turn it over and start printing the copper electrode. After the copper electrode is printed, let it cool and stand for 3 hours again, and finally take it out of the argon environment to obtain a cement-based zinc battery with low interfacial impedance.
[0072] Example 2
[0073] In this embodiment, a cement-based zinc battery with low interfacial impedance is provided, comprising the following components in parts by weight:
[0074]
[0075] In this embodiment, the cementitious material includes the following components in percentage by mass: 80% silicate cement, 10% fly ash, and 10% silica fume.
[0076] The water reducer is a polycarboxylate water reducer, specifically a high early strength polycarboxylate water reducer.
[0077] The modifier includes the following components in percentage by mass: 60% of polyacrylamide and 40% of bentonite, wherein the weight average molecular weight of the polyacrylamide is 10 million Daltons.
[0078] The early strength agent includes the following components in percentage by mass: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5.
[0079] The cement-based zinc battery with low interfacial impedance is prepared by the following steps:
[0080] First, 200 parts of cementitious material, 0.4 parts of water reducer, 15 parts of early strength agent and 80 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 24 hours until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 0-4°C for 30 hours to obtain block C, and block C is placed in a cement standard curing box for curing for 28 days to obtain a cement-based material D with a directional pore structure. Cement-based material D is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain cement-based material E.
[0081] After wiping off the liquid on the surface of cement-based material E, a steel brush was used to remove the passivation layer and impurities on the surface of cement-based material E to obtain cement-based material F. Figure 1 and 2 As shown, a fixed laser scanner is used to scan and model the surface of cement-based material F. The model data is processed and converted and then input into a coaxial powder feeding 3D printer. 2.5 parts of zinc powder and 3 parts of copper powder are added to the 3D printer silo respectively. The cement-based material F and the 3D printer are placed in an argon environment for printing. The 3D printer used has a laser power of 2KW and a printing speed of 5mm / s. In an argon protective environment, the 3D printer is started to ensure that the oxygen content in the printing area is controlled below 50ppm to avoid metal oxidation. The control system activates the printing program based on the imported model data. The initial printing starts from the center of the surface of the cement-based material F and proceeds along a rectangular circumferential route (such as Figure 2 As shown). The print head adjusts its height according to the modeling data, with the starting distance being 0.1mm above the highest point on the surface. Due to the different heights of each position, the amount of powder output changes accordingly, and finally the first layer of metal smoothly covers the surface, followed by layer-by-layer printing to form an actual working electrode thickness of 2-3mm. After printing the zinc electrode, let it stand and cool for 3 hours, then turn it over and start printing the copper electrode. After the copper electrode is printed, let it cool and stand for 3 hours again, and finally take it out of the argon environment to obtain a cement-based zinc battery with low interfacial impedance.
[0082] Example 3
[0083] In this embodiment, a cement-based zinc battery with low interfacial impedance is provided, comprising the following components in parts by weight:
[0084]
[0085] In this embodiment, the cementitious material includes the following components in percentage by mass: 80% silicate cement, 10% fly ash, and 10% silica fume.
[0086] The water reducer is a polycarboxylate water reducer, specifically a high early strength polycarboxylate water reducer.
[0087] The modifier includes the following components in percentage by mass: 60% of polyacrylamide and 40% of bentonite, wherein the weight average molecular weight of the polyacrylamide is 10 million Daltons.
[0088] The early strength agent includes the following components in percentage by mass: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5.
[0089] The cement-based zinc battery with low interfacial impedance is prepared by the following steps:
[0090] First, 200 parts of cementitious material, 0.4 parts of water reducer, 15 parts of early strength agent and 120 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 24 hours until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 0-4°C for 30 hours to obtain block C, and block C is placed in a cement standard curing box for curing for 28 days to obtain a cement-based material D with a directional pore structure. Cement-based material D is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain cement-based material E.
[0091] After wiping off the liquid on the surface of cement-based material E, a steel brush was used to remove the passivation layer and impurities on the surface of cement-based material E to obtain cement-based material F. Figure 1 and 2 As shown, a fixed laser scanner is used to scan and model the surface of cement-based material F. The model data is processed and converted and then input into a coaxial powder feeding 3D printer. 2.5 parts of zinc powder and 3 parts of copper powder are added to the 3D printer silo respectively. The cement-based material F and the 3D printer are placed in an argon environment for printing. The 3D printer used has a laser power of 2KW and a printing speed of 5mm / s. In an argon protective environment, the 3D printer is started to ensure that the oxygen content in the printing area is controlled below 50ppm to avoid metal oxidation. The control system activates the printing program based on the imported model data. The initial printing starts from the center of the surface of the cement-based material F and proceeds along a rectangular circumferential route (such as Figure 2As shown). The print head adjusts its height according to the modeling data, with the starting distance being 0.1mm above the highest point on the surface. Due to the different heights of each position, the amount of powder output changes accordingly, and finally the first layer of metal smoothly covers the surface, followed by layer-by-layer printing to form an actual working electrode thickness of 2-3mm. After printing the zinc electrode, let it stand and cool for 3 hours, then turn it over and start printing the copper electrode. After the copper electrode is printed, let it cool and stand for 3 hours again, and finally take it out of the argon environment to obtain a cement-based zinc battery with low interfacial impedance.
[0092] Comparative Example 1
[0093] In this comparative example, a cement-based zinc battery is provided, comprising the following components in parts by weight:
[0094]
[0095]
[0096] The cementitious material in this comparative example includes the following components in percentage by mass: 80% of silicate cement, 10% of fly ash, and 10% of silica fume.
[0097] The water reducer is a polycarboxylate water reducer, specifically a high early strength polycarboxylate water reducer.
[0098] The modifier includes the following components in percentage by mass: 60% of polyacrylamide and 40% of bentonite, wherein the weight average molecular weight of the polyacrylamide is 10 million Daltons.
[0099] The early strength agent includes the following components in percentage by mass: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5.
[0100] The cement-based zinc battery is prepared by the following steps:
[0101] First, 200 parts of cementitious material, 0.4 parts of water reducing agent, 15 parts of early strength agent and 100 parts of water were placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier were placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A was poured into a mold with a heat-conducting template at the bottom to obtain block B, and block B was placed in a cement standard curing box for curing for 28 days to obtain cement-based material C. Cement-based material C was soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain cement-based material D.
[0102] After wiping off the liquid on the surface of cement-based material D, the passivation layer and impurities on the surface of cement-based material E were removed with a steel brush to obtain cement-based material E. Figure 1As shown, a fixed laser scanner is used to scan and model the surface of cement-based material E. The model data is processed and converted and then input into a coaxial powder feeding 3D printer, and 2.5 parts of zinc powder and 3 parts of copper powder are added to the 3D printer silo respectively. The cement-based material E and the 3D printer are placed in an argon environment for printing. The laser power of the 3D printer used is 2KW and the printing speed is 5mm / s. In an argon protection environment, the 3D printer is started to ensure that the oxygen content in the printing area is controlled below 50ppm to avoid metal oxidation. The control system activates the printing program according to the imported model data. The initial printing starts from the center of the sample and proceeds along a rectangular circumferential route. The print head adjusts the height according to the modeling data, and the starting distance is 0.1mm above the highest point on the surface. Due to the different heights of each position, the powder output changes accordingly, and finally the first layer of metal smoothly covers the surface, and then prints layer by layer to form an actual working electrode thickness of 2-3mm. After printing the zinc electrode, let it stand and cool for 3 hours, then turn it over and start printing the copper electrode. After the copper electrode is printed, let it cool and stand for 3 hours again, and finally take it out of the argon environment to obtain a cement-based zinc battery.
[0103] Comparative Example 2
[0104] In this comparative example, a cement-based zinc battery is provided, comprising the following components in parts by weight:
[0105]
[0106] The cementitious material in this comparative example includes the following components in percentage by mass: 80% of silicate cement, 10% of fly ash, and 10% of silica fume.
[0107] The water reducer is a polycarboxylate water reducer, specifically a high early strength polycarboxylate water reducer.
[0108] The modifier includes the following components in percentage by mass: 60% of polyacrylamide and 40% of bentonite, wherein the weight average molecular weight of the polyacrylamide is 10 million Daltons.
[0109] The early strength agent includes the following components in percentage by mass: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5.
[0110] The cement-based zinc battery is prepared by the following steps:
[0111] First, 200 parts of cementitious material, 0.4 parts of water reducer, 15 parts of early strength agent and 100 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 24 hours until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 0-4°C for 30 hours to obtain block C, and block C is placed in a cement standard curing box for curing for 28 days to obtain a cement-based material D with a directional pore structure. Cement-based material D is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain cement-based material E.
[0112] After wiping the liquid on the surface of cement-based material E, the passivation layer and impurities on the surface of cement-based material E were removed with a steel brush to obtain cement-based material F. A zinc sheet with a thickness of 3 mm and a copper sheet with a thickness of 3 mm were pressed on both sides of cement-based material E at a pressure of 1.5 MPa to obtain a cement-based zinc battery.
[0113] Comparative Example 3
[0114] In this comparative example, a cement-based zinc battery is provided, comprising the following components in parts by weight:
[0115]
[0116]
[0117] The cementitious material in this comparative example includes the following components in percentage by mass: 80% of silicate cement, 10% of fly ash, and 10% of silica fume.
[0118] The water reducer is a polycarboxylate water reducer, specifically a high early strength polycarboxylate water reducer.
[0119] The modifier includes the following components in percentage by mass: 60% of polyacrylamide and 40% of bentonite, wherein the weight average molecular weight of the polyacrylamide is 10 million Daltons.
[0120] The early strength agent includes the following components in percentage by mass: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5.
[0121] The cement-based zinc battery is prepared by the following steps:
[0122] First, 200 parts of cementitious material, 0.4 parts of water reducer, 15 parts of early strength agent and 100 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 24 hours until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 0-4°C for 30 hours to obtain block C, and block C is placed in a cement standard curing box for curing for 28 days to obtain a cement-based material D with a directional pore structure. Cement-based material D is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain cement-based material E.
[0123] After wiping the liquid on the surface of cement-based material E, the passivation layer and impurities on the surface of cement-based material E were removed with a steel brush to obtain cement-based material F. 2.5 parts of zinc powder and 3 parts of copper powder were placed in a tubular muffle furnace filled with argon, and the zinc powder was heated to 500°C to melt, and the copper powder was heated to 1200°C to melt. In a glove box filled with argon, molten zinc or copper was directly poured on the surface of cement-based material E. After pouring the zinc electrode, it was allowed to cool for 3 hours, then turned over and the copper electrode was cast. After the copper electrode was cast, it was cooled and allowed to stand for 3 hours again, and finally it was taken out of the argon environment to obtain a cement-based zinc battery.
[0124] Referring to the national standard "Test Method for Cement Mortar Strength (ISO Method)" (GB / T17671-2021), the 40mm×40mm×160mm cement-based electrolyte samples prepared in the above Examples 1-3 and Comparative Examples 1-3 were subjected to compression tests, and the testing instrument was a universal testing machine. The electrochemical impedance spectroscopy was used to study the interface impedance, and the electrolyte ion conductivity and the electrode and electrolyte cross-sectional impedance were obtained by fitting and calculation. At 25°C, 1mA / cm 2 The coulombic efficiency of cement-based zinc batteries was tested after 10,000 cycles at a current density of .
[0125] Table 1 Performance of cement-based zinc batteries prepared in Examples 1-3 and Comparative Examples 1-3
[0126]
[0127] As can be seen from Table 1, compared with Comparative Example 1, the ionic conductivity of the cement-based electrolyte with a directional pore structure obtained by the freeze casting technology in the present invention, i.e., Example 1, is higher, and the electrode is printed on the surface of the cement-based electrolyte by 3D printing technology, which greatly improves the interface impedance between the electrolyte and the electrode. At the same time, since the 3D printing technology allows the liquid metal electrode material to directly enter the micro-cracks on the surface of the cement-based electrolyte, the adhesion strength between the cement-based electrolyte and the metal electrode is greatly improved, thereby reducing the possibility of separation at the interface under working conditions. Therefore, compared with Comparative Examples 1, 2, and 3, the coulomb efficiency of Examples 1-3 can still be maintained at 90% or more after 10,000 cycles, and has good stability.
[0128] In summary, the cement-based zinc battery prepared by the present invention has low interfacial impedance and long-term stability during use, which improves the overall performance of the battery and can be applied to building structures to alleviate dependence on traditional energy storage devices.
[0129] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A cement-based zinc battery with low interfacial impedance, characterized in that: The cement-based zinc battery includes a cement-based electrolyte, and a positive electrode material layer and a negative electrode material layer are respectively melt-solidified on opposite sides of the surface of the cement-based electrolyte by 3D printing technology.
2. A cement-based zinc battery with low interfacial impedance according to claim 1, characterized in that: The vertical height of the cement-based electrolyte is 15-20 mm, and the cement-based electrolyte has a directional pore structure with a pore diameter of 10-20 μm and a porosity of 25-40%.
3. A cement-based zinc battery with low interfacial impedance according to claim 2, characterized in that: The pores of the directionally arranged pore structure are oriented in the same direction as the vertical direction of the cement-based electrolyte. The positive electrode material layer and the negative electrode material layer are respectively melt-solidified on both sides of the vertical direction of the cement-based electrolyte. The positive electrode material layer is copper with a thickness of 2-3 mm; the negative electrode material layer is zinc with a thickness of 2-3 mm.
4. A cement-based zinc battery with low interfacial impedance according to claim 1, characterized in that: The composition includes the following components in parts by weight:
5. A cement-based zinc battery with low interfacial impedance according to claim 4, characterized in that: The cementitious material is selected from any one or more of silicate cement, fly ash, and silica fume; The water reducer is selected from any one or more of polycarboxylate water reducer and lignin sulfonate; The modifier is selected from any one or more of polyacrylamide and bentonite; The early strength agent is selected from any one or more of gypsum and water glass; The particle size of the zinc powder is in the range of 45-150 μm; The particle size of the copper powder is in the range of 45-150 μm.
6. A method for preparing a cement-based zinc battery with low interfacial impedance according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: S1, immersing cement-based material D in a zinc sulfate solution to obtain cement-based material E; S2, removing impurities on the surface of the cement-based material E, and after cleaning the surface, obtaining the cement-based electrolyte; S3, using a fixed laser scanner to scan and model the surface of the cement-based electrolyte, and inputting the obtained model data into a coaxial powder feeding 3D printer; S4. In an inert gas environment, a zinc electrode material layer and a copper electrode material layer are printed on opposite sides of the cement-based electrolyte by a coaxial powder feeding 3D printer to obtain the cement-based zinc battery with low interfacial impedance.
7. The method for preparing a cement-based zinc battery with low interfacial impedance according to claim 6, characterized in that: In step S4, The inert gas environment includes an argon environment; After the zinc electrode material layer is printed, let it stand and cool for 2-4 hours, then turn the cement-based electrolyte over and start printing the copper electrode material layer on the opposite side. After the copper electrode material layer is printed, let it stand and cool for another 2-4 hours. The parameters of the 3D printing are: printing speed 5-10 mm / s, printing height 2-3 mm, and printing time 60-80 min.
8. The method for preparing a cement-based zinc battery with low interfacial impedance according to claim 6, characterized in that: In step S1, the concentration of the zinc sulfate solution is 1-2M, and the immersion time is 24-48 hours.
9. The method for preparing a cement-based zinc battery with low interfacial impedance according to claim 6, characterized in that: In step S1, the cement-based material D is prepared by the following steps: S1.
1. Mix the cementitious material, water reducing agent, early strength agent and water according to their mass proportions and stir evenly, then add the modifier and stir evenly to obtain slurry A; S1.
2. Pour slurry A into a mold with a heat conducting plate at the bottom and let it stand; S1.3, placing the mold containing slurry A on an ultra-low temperature medium for freeze casting to quickly obtain solidified cement slurry B; S1.
4. Thaw the solidified cement paste B to obtain a block C, and then place the block C in a standard cement curing box for curing for 24 to 30 days to obtain a cement-based material D having a directional pore structure.
10. Use of a cement-based zinc battery with low interfacial impedance as claimed in any one of claims 1 to 5 in the field of building materials.
Citation Information
Patent Citations
Method for manufacturing solid-state battery by using 3D printing technology
CN114583283A
Manufacturing method of low-interface resistance solid-state battery
CN115224369A
Cement-based material with high ion mobility as well as preparation method and application of cement-based material
CN118652085A
Cement-based energy storage structure and preparation method thereof
CN118983192A
System and method for 3D printing porous zinc structures
US20230132546A1